The Influence of Creativity and Competence on Teacher’s Performance - Wati, Adri Panca; Fitria, Happy; Fitriani, Yessi (Journal of Social Work and Science Education, 2024)
The purpose of this study was to examine the influence of creativity and competence on the performance of Early Childhood Teachers in Lubuk Besar District, Central Bangka Regency. The sample size taken was 53 early childhood education program (PAUD) teachers in Lubuk Besar District, Central Bangka Regency. The sampling technique was purposive sampling, namely, where the respondents who were taken were some PAUD teachers in Lubuk Besar District, Central Bangka Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 90 statement items. The analysis technique used is multiple linear regression analysis. The results of the study show that there is an influence of teacher creativity on teacher performance. Second, there is an influence of teacher competence on teacher performance. Second, there is a simultaneous influence of teacher creativity and teacher competence on teacher performance.